2018
DOI: 10.1097/mcg.0000000000000820
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Evaluation of Adherence to 4 Major Elements of the Baveno Guidelines and Outcomes for Patients With Acute Variceal Hemorrhage

Abstract: Adherence to quality metrics may not reduce the risk of mortality but could improve secondary outcomes of AVH. Variation in practice should be addressed through quality improvement interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Among the patients with MELD score ≤17, early endoscopy could have worse outcomes than delayed endoscopy [21]. According to the present work, only four studies [8,[19][20][21] clearly demonstrated that the baseline characteristics of patients were not significantly different between early and delayed endoscopy groups, but the remaining five studies [7,[15][16][17][18] did not mention the difference in the severity of liver dysfunction between the two groups, which might lead to a potential bias in the statistical results. Additionally, we could not extract any relevant data to stratify the impact of timing of endoscopy on the basis of the severity of liver cirrhosis.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Among the patients with MELD score ≤17, early endoscopy could have worse outcomes than delayed endoscopy [21]. According to the present work, only four studies [8,[19][20][21] clearly demonstrated that the baseline characteristics of patients were not significantly different between early and delayed endoscopy groups, but the remaining five studies [7,[15][16][17][18] did not mention the difference in the severity of liver dysfunction between the two groups, which might lead to a potential bias in the statistical results. Additionally, we could not extract any relevant data to stratify the impact of timing of endoscopy on the basis of the severity of liver cirrhosis.…”
Section: Discussionmentioning
confidence: 64%
“…Chen et al showed that early endoscopy had lower 6-week mortality than delayed endoscopy in the hematemesis group; contrarily, the 6-week mortality was similar between them in the nonhematemesis group [7]. Of our included studies, 2 clearly reported the proportion of hematemesis in each group [20,21], 3 just reported the proportion of hematemesis in total patients [7,8,15], and 4 did not mention the manifestations of AVB [16][17][18][19]. Thus, the present meta-analysis could not explore the impact of timing of endoscopy in patients with different manifestations of AVB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that cirrhotic patients who receive a treatment adherent to CPG recommendations could benefit from good therapeutic efficacy [ 7 ]. Moreover, a multicenter evaluation study found that adherence to Baveno CPGs could improve the clinical outcomes of patients with acute variceal haemorrhage [ 8 ]. Several CPGs have been developed for the management of bacterial infections in patients with cirrhosis or liver failure.…”
Section: Introductionmentioning
confidence: 99%